Forebrain corticosteroid receptors promote post-myocardial infarction depression and mortality - Bruns, Bastian; Daub, Ricarda; Schmitz, Thomas; Hamze Sinno, Maria; Spaich, Sebastian; Dewenter, Matthias; Schwale, Chrysovalandis; Gass, Peter; Vogt, Miriam; Katus, Hugo; Herzog, Wolfgang; Friederich, Hans-Christoph; et al. (Basic research in cardiology, 2022)
Myocardial infarction (MI) with subsequent depression is associated with increased cardiac mortality. Impaired central mineralocorticoid (MR) and glucocorticoid receptor (GR) equilibrium has been suggested as a key mechanism in the pathogenesis of human depression. Here, we investigate if deficient central MR/GR signaling is causative for a poor outcome after MI in mice. Mice with an inducible forebrain-specific MR/GR knockout (MR/GR-KO) underwent baseline and follow-up echocardiography every 2 weeks after MI or sham operation. Behavioral testing at 4 weeks confirmed significant depressive-like behavior and, strikingly, a higher mortality after MI, while cardiac function and myocardial damage remained unaffected. Telemetry revealed cardiac autonomic imbalance with marked bradycardia and ventricular tachycardia (VT) upon MI in MR/GR-KO. Mechanistically, we found a higher responsiveness to atropine, pointing to impaired parasympathetic tone of ‘depressive’ mice after MI. Serum corticosterone levels were increased but—in line with the higher vagal tone—plasma and cardiac catecholamines were decreased. MR/GR deficiency in the forebrain led to significant depressive-like behavior and a higher mortality after MI. This was accompanied by increased vagal tone, depleted catecholaminergic compensatory capacity and VTs. Thus, limbic MR/GR disequilibrium may contribute to the impaired outcome of depressive patients after MI and possibly explain the lack of anti-depressive treatment benefit.